Female unemployment and the procedure that a woman has to go through to start a business: microfinance policy thresholds - Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
This study examines how the starting of business by females can be promoted by assessing critical levels of microfinance institutions (MFIs) penetration that policy makers must endeavour to maintain and/or attain in order for female unemployment not to represent a constraint in the doing of business. A constraint in doing business is understood in terms of the procedure that a woman has to go through in order to start a business. The focus of the study is on 44 countries in Sub-Saharan Africa (SSA) for the period 2004-2018, while the empirical evidence is based on interactive quantile regressions. The following findings are established. The validity of tested hypotheses is exclusively apparent in the lowest and highest quantiles of the conditional distribution of the procedure women have to go through to start a business. MFI penetration levels needed to reverse the unfavorable incidence of female unemployment in doing business are provided. These are minimum MFIs penetration thresholds that are required in order for female unemployment not to negatively affect the procedure that a woman should go through to start a business. The study complements the extant literature by assessing critical microfinance penetration levels that are needed to promote female doing of business, contingent on existing levels of female doing of business.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Microfinance; Gender; Inclusive development